The role of fintech in financing startups with reference to the cases of Algeria and France - hami, bakir; goudjil, Mehamed (Journal of Research in Finance and Accounting, 2024)
This study aims to clarify the concept and importance of fintech, focusing on funding platforms such as crowdfunding, debt and equity, and how startups can benefit from it. The study relied on a descriptive, analytical and quantitative approach to collect data on the impact of financial technology on financing startups in Algeria, and the study found that financial technology contributes to facilitating access to funding in innovative ways, which opens up more flexible opportunities for startups and helps reduce costs associated with financing and financial management, such as the use of blockchain technologies, and it also provides new opportunities to provide innovative financial services, such as digital banks and e-wallets.